1998
DOI: 10.1002/(sici)1097-0215(19980130)75:3<412::aid-ijc15>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of cells with different metastatic potentials by liposome-delivered Zn(II)-phthalocyanine

Abstract: The phototoxicity of liposome‐incorporated Zn(II)‐phthalocyanine (ZnPc) and its water‐soluble tetrasulphonated derivative (ZnPcTS) was studied in the tumorigenic but nonmetastatic (RE4) and the highly metastatic (4R) transformed rat embryo fibroblasts. Upon irradiation with 585–605 nm light in the presence of ZnPc, the cell survival drastically decreased, while it was unaffected by ZnPcTS. Enzymatic assays showed that ZnPc induced about a 60% decrease in the activity of the mitochondrial enzymes NADH and succi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
(19 reference statements)
0
11
1
6
Order By: Relevance
“…By contrast with other reports (Rodal et al 1998, Valduga et al 1998, Alexandratou et al 2005) that described localization of ZnPc also in mitochondria or plasma membrane of other cell lines, we observed no accumulation of the drug in these organelles of A-549 cells. According to Fabris et al (2001), the Golgi apparatus of transformed rat fibroblast cell line 4R was labeled after ZnPc incubation for 2 h, whereas after 24 h incubation, labeling occurred in both Golgi region and mitochondria.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By contrast with other reports (Rodal et al 1998, Valduga et al 1998, Alexandratou et al 2005) that described localization of ZnPc also in mitochondria or plasma membrane of other cell lines, we observed no accumulation of the drug in these organelles of A-549 cells. According to Fabris et al (2001), the Golgi apparatus of transformed rat fibroblast cell line 4R was labeled after ZnPc incubation for 2 h, whereas after 24 h incubation, labeling occurred in both Golgi region and mitochondria.…”
Section: Discussioncontrasting
confidence: 99%
“…1) on cultured cells is a well-known feature that results in cell death by apoptotic or necrotic mechanisms (Villanueva et al 1999, Fabris et al 2001, Galaz et al 2005. Different localization sites for ZnPc in living cells have been reported including lysosomelike granules and diffuse cytoplasm (Rü ck et al 1996), plasma membrane (Valduga et al 1998), Golgi apparatus and mitochondria (Rodal et al 1998, Fabris et al 2001, mitochondria (Alexandratou et al 2005), and Golgi region (Cristó bal et al 2006, Rello-Varona et al 2008. Accounting for these differences, the aim of the study reported here was to analyze the subcellular localization of ZnPc more precisely using a co-localization procedure with NBD C 6 -ceramide ( Fig.…”
mentioning
confidence: 99%
“…Cell survival was tested by a clonogenic assay, as described previously (28). HT-1080, treated 16 hours with 3, 9, and 27 mol/L Hyp-DCHA as described above, were trypsinized, suspended in Hyp-DCHA-free medium, and tested for viability (parallel controls); 50 to 100 cells (depending on the survival percentage) were then reseeded in sextuplicates into 3.5-cm diameter plastic wells precoated overnight with FCS.…”
Section: Long-term Clonogenicitymentioning
confidence: 99%
“…Another study involving cationic substituted Zn(II) phthalocyanines, bearing anilinium groups in different positions, showed a Staphylococcus aureus survival decrease of ≈4.6 log, without affecting fibroblasts, when a concentration of 0.1 μ m and a total light dose of 15 J·cm −2 delivered at the fluence rate of 50 mW·cm −2 of red light was used (24). Regarding cancer PDT, Zn(II) phthalocyanine presented an efficient selectivity and photosensitization of MS‐2 fibrosarcoma (21) and its liposome‐incorporated preparation also affected drastically cell survival of tumorigenic non‐ and highly metastic transformed rat fibroblasts (22). Plus, a liposomal preparation of zinc phthalocyanine (CGP55847) has undergone clinical trials (Phase I/II, Switzerland) against squamous cell carcinomas of the upper aerodigestive tract (23).…”
Section: Introductionmentioning
confidence: 99%